New brain tumor entities emerge from molecular classification of CNS-PNETs - Sturm, Dominik; Orr, Brent A.; Toprak, Umut; Hovestadt, Volker; Jones, David T. W.; Capper, David; Sill, Martin; Buchhalter, Ivo; Northcott, Paul A.; Leis, Irina; Ryzhova, Marina; Kölsche, Christian; et al. (Cell, 2016)
Primitive neuroectodermal tumors of the central nervous system (CNS-PNETs) are highly aggressive, poorly differentiated embryonal tumors occurring predominantly in young children but also affecting adolescents and adults. Herein, we demonstrate that a significant proportion of institutionally diagnosed CNS-PNETs display molecular profiles indistinguishable from those of various other well-defined CNS tumor entities, facilitating diagnosis and appropriate therapy for patients with these tumors. From the remaining fraction of CNS-PNETs, we identify four new CNS tumor entities, each associated with a recurrent genetic alteration and distinct histopathological and clinical features. These new molecular entities, designated “CNS neuroblastoma with FOXR2 activation (CNS NB-FOXR2),” “CNS Ewing sarcoma family tumor with CIC alteration (CNS EFT-CIC),” “CNS high-grade neuroepithelial tumor with MN1 alteration (CNS HGNET-MN1),” and “CNS high-grade neuroepithelial tumor with BCOR alteration (CNS HGNET-BCOR),” will enable meaningful clinical trials and the development of therapeutic strategies for patients affected by poorly differentiated CNS tumors.
Gesehen am 23.10.2019